Aspek Penerapan Manajemen Risiko Untuk Industri 4.0 - Defi Seftiana; Sabrina Yolanda Br Nainggolan; Shakira Alaya; Putri Kemala Dewi Lubis; Rossy Pratiwi Sihombing (Pusat Riset dan Inovasi Nasional, 2024)
Industry 4.0 is a relatively new method of managing production processes. In the field of risk management, as a result of new approaches, modified frameworks, more complex IT infrastructure, and so on, new types of risks may appear. In many cases, the application of Industry 4.0 has shown that the relationship between people, systems, and objects has become a more complex, dynamic, and real-time optimized network. On the other hand, there is the fact that the increase in the volume and availability of data in real time has led to new requirements on infrastructure, management, technology and so on. The purpose of this paper is to conduct research on Industry 4.0 related to the main aspects and present a draft framework for implementing risk management in the Industry 4.0 concept.